A Comprehensive Review-Remote Monitoring System Based on Iomt for Neurological Disabilities - Raj M S, Pradeep; P, Manimegalai (Malikussaleh University, Aceh, Indonesia, 2025)
The vital source of the Internet of Things (IoT) in medical industries is said to be the Internet of Medical Things (IoMT). Currently, IoMT has exponential growth in remote monitoring systems (RMS), mainly for neurological disability patients. The main aim of IoMT is to proliferate the factors of electronic devices such as trustworthiness, efficiency, and accuracy. There exists enormous ongoing research in IoMT in this area, and huge devices are being approached. However, there are different types of neurological disabilities (ND) around the world, and countable IoMT remote monitoring systems were developed for the most common neurological problems. So, this article is fully concentrated on the study of different neurological problems and the RMS-IoMT. This review is essential for many biomedical and medical researchers, and it deals with the doctor’s opinion and the importance of the IoMT system, common neurological disabilities, and the RMS-IoMT system’s merits and demerits for neuro disorders.